PRAWN FISHERY OF ALLEPPEY COAST DURING THE S.W. MONSOONS OF 1972-1976 - Kurup, P Surendranatha (Indian Journal of Fisheries, 2011)
the same season and also duting the corresponding months of different seasons. The prawn catch was mainly constituted by Metapenaeus dobsoni (Miers). June-July months were more productive on account of recruitment of more individuals belonging to higher size groups. The monthly average mean sizes of M. dobsoni showed great disparity, ranging between 75.2 mm and 91.5 mm for males and 81.3 mm and 103.4 mm for females. In the species, males were found in a higher proportion than females in lower size groups, but females occurred in higher proportions in higher size groups. The recruitment of mature females into the fishery was quite irregular throughout the seasons of different years under study. The analysis of stomach